The acute effects of weighted vest protocols on 20-metre sprint performance in youth soccer players - Bright, T.; Hughes, J.; Handford, M.; Anniss, B.; Westwood, C. (International Journal of Strength and Conditioning, 2022)
This investigation examined the effects of a warm-up containing weighted vest (WV) sprints on subsequent 20-metre sprint time relative to a control (C) condition in youth soccer players (n=12, mean ± SD age 16 ± 0.60 years, height 175.17 ± 5.92 cm and body mass 61.85 ± 5.88 kg). The main experimental trials consisted of three WV conditions at 10, 20 and 30% of body mass (WV10, WV20 and WV30) and C. Participants were required to complete one 20-metre sprint with each of WV conditions or without additional mass as part of C prior to a 20-metre sprint at 4-, 8- and 12-minutes. A two-way repeated measures ANOVA revealed no significant difference between any of the conditions and rest periods (p = >0.05). The between condition effect sizes for 20-metre sprint times were moderate at 4- and 12-minutes post WV10 (d = -0.86 and -1.15, respectively) and 12-minutes post WV20 (d = -0.84) and WV30 (d = -0.80). Moderate effect sizes were also observed at 4-minutes post WV10 (d = -1.04) and WV20 (d = -0.67) for 10-metre sprint times. These findings demonstrate that WV loading has no significant effect on 20-metre sprint time in youth soccer players. However, there is an opportunity for S&C coaches to implement WV warm-ups of no more than 30% body mass to improve 20-metre sprint times.